Challenge and path of high-quality development of coal mine intelligent construction - Guofa WANG; Huaiwei REN; Jiaxing FU (Meitan kexue jishu)
Coal mine intelligentization is a vital direction for promoting the high-quality development of the coal industry. Reviews advancements in the foundational theories, technological systems, and demonstration applications of coal mine intelligentization, comprehensively analyzes the current status of intelligent coal mine construction, identifies key technological bottlenecks, and proposes pathways to address these challenges. In terms of foundational theories, the study focuses on the theoretical framework of digital coal mines and intelligent mining. For technological system construction, the key technical modules of intelligent coal mines are summarized. Regarding demonstration applications, typical intelligent mines are used as case studies to evaluate the application effects of intelligent systems in actual production and to identify technical, managerial encountered during their promotion. Building upon in-depth research into the foundational theories and technological systems of coal mine intelligentization, as well as practical experiences from demonstration mines, the study systematically examines the current status and pressing issues in intelligent geological support, information and communication systems, excavation, mining, and intelligent safety control systems. Special attention is given to addressing technological bottlenecks in efficient excavation under complex geological conditions, high-efficiency mining of thin coal seams and seams prone to dynamic pressure, robotic collaborative operations, and system maintenance. The research highlights the development of efficient excavation technologies for complex conditions, high-performance mining techniques for thin coal seams and dynamic-pressure coal seams, critical technologies for coal mine robotics, and innovations in next-generation intelligent safety control systems. It further emphasizes accelerating the large-scale and intelligent transformation of open-pit coal mines, improving the standardization of intelligent mine operation and maintenance systems, and facilitating iterative upgrades to intelligent systems. Driven by industry needs and guided by technological innovation, the study advocates for the integration, advancement, and digitalization of coal mining equipment to provide reliable technological and equipment support for the high-quality and sustainable development of coal mine intelligentization.